Sonographic Evaluation of Breast Nodules: Comparison of Conventional, Real-Time Compound, and Pulse-Inversion Harmonic Images - Seo, Bo-Kyoung (The Korean Radiological Society, 2002)
OBJECTIVE: To compare the use of conventional, real-time compound, and pulse-inversion harmonic imaging in the evaluation of breast nodules. MATERIALS AND METHODS: Fifty-two breast nodules were included in this study, conducted between May and December 2000, in which conventional, real-time compound, and pulse-inversion harmonic images were obtained in the same plane. Three radiologists, each blinded to the interpretations of the other two, evaluated the findings, characterizing the lesions and ranking the three techniques from grade 1, the worst, to grade 3, the best. Lesion conspicuity was assessed, and lesions were also characterized in terms of their margin, clarity of internal echotexture, and clarity of posterior echo pattern. The three techniques were compared using Friedman's test, and interobserver agreement in image interpretation was assessed by means of the intraclass correlation coefficient. RESULTS: With regard to lesion conspicuity, margin, and internal echotexture of the nodules, real-time compound imaging was the best technique (p < 0.05); in terms of posterior echo pattern, the best was pulse-inversion harmonic imaging (p < 0.05). Real-time compound and pulse inversion harmonic imaging were better than conventional sonography in all evaluative aspects. Interobserver agreement was greater than moderate. CONCLUSION: Real-time compound and pulse-inversion harmonic imaging procedures are superior to conventional sonography in terms of both lesion conspicuity and the further characterization of breast nodules. Real-time compound imaging is the best technique for evaluation of the margin and internal echotexture of nodules, while pulse-inversion harmonic imaging is very effective for the evaluation of the posterior echo patterns.